The genus Cymodoce Leach, 1814 (Crustacea: Isopoda: Sphaeromatidae) in the Persian Gulf with description of a new species - Khalaji-Pirbalouty, Valiallah; Bruce, Niel L.; Wägele, Johann-Wolfgang (Zootaxa, 2013)
Cymodoce truncata (Leach, 1814), the type species of the genus, C. zanzibarensis (Stebbing, 1910) and C. richardsoniae (Nobili, 1906) are redescribed based on type specimens or topotypic material, and a neotype is designated for Cymodoce richardsoniae. A revised generic diagnosis and description is provided for the genus Cymodoce. Cymodoce delvarii sp. nov. is described from the subtidal zone of the Iranian coasts of the Persian Gulf.